The role of agro‐ecological factors and transboundary transhumance in shaping the genetic diversity in four indigenous cattle populations of Benin. (16th July 2020) - Scheper, Carsten; Bohlouli, Mehdi; Brügemann, Kerstin; Weimann, Christina; Vanvanhossou, Sèyi Fridaïus Ulrich; König, Sven; Dossa, Luc Hippolyte
Abstract: The indigenous cattle population of Benin is a diverse mix of taurine and hybrid breeds shaped by diverse ecological and climatic conditions with eight agro‐ecological zones (AEZ). Presumably, the taurine breeds face current endangerment due to ongoing indicine introgression following climate change and transboundary transhumance. The aim of the study was to investigate the genetic diversity and population structure of the indigenous breeds Lagune, Somba, Pabli and Borgou considering spatial agro‐ecological and socio‐economic factors (transhumance) based on 50k SNP and microsatellite data. Among the four sampled breeds, six genetic clusters were identified using model‐free (discriminant analysis of principal components) and model‐based (TESS and ADMIXTURE) methods separating taurine from hybrid breeds. Results based on an extension with publicly available historic SNP data sets from taurine and indicine West African cattle and additional outgroups provided additional insight into changes of genetic structure in the sampled breeds over time. Both taurine breeds, Somba and Lagune, showed a stable foundation but also spatially limited partial indicine introgression associated with transhumance leading to high genetic diversity. In addition, we found evidence for spatial diversity and changes in genetic structure over time in the Borgou breed in comparison of our samples with the historic samples which could be explained by potential continuous indicine introgression into the Borgou breed in two sample regions. Results for the Pabli breed do not conclusively point to full absorbance by the Borgou in comparison with all available Borgou samples. Further research is needed in this regard.